2015
DOI: 10.2134/cftm2014.0050
|View full text |Cite
|
Sign up to set email alerts
|

Annual Bluegrass Control on Putting Greens from Three or Four Years of Season‐long Applications of Herbicides or Plant Growth Regulators in Three States

Abstract: Annual bluegrass (Poa annua L.) may be the most troublesome and studied weed on golf courses in the United States. Given the genetic variability of annual bluegrass and its ability to adapt to different environments, it is important to understand how control methods vary across environments or regions. Our objective was to evaluate seven season‐long regimes of herbicide or growth regulators for annual bluegrass control in creeping bentgrass (Agrostis stolonifera Huds.) putting greens over 3 or 4 years in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…Askew et al (2004) and McCullough and Hart (2006) reported that bispyribac‐sodium was another effective herbicide for controlling ABG in cool‐season turf maintained at fairway height. Reicher et al (2015) did not report any injury from bispyribac‐sodium applications to putting greens in summer, but efficacy for ABG control was inconsistent across locations. Others have reported injury from applications of bispyribac‐sodium to creeping bentgrass, especially applications in the spring or fall or at cooler temperatures (Lycan and Hart, 2006; McCullough and Hart, 2006).…”
Section: Useful Conversionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Askew et al (2004) and McCullough and Hart (2006) reported that bispyribac‐sodium was another effective herbicide for controlling ABG in cool‐season turf maintained at fairway height. Reicher et al (2015) did not report any injury from bispyribac‐sodium applications to putting greens in summer, but efficacy for ABG control was inconsistent across locations. Others have reported injury from applications of bispyribac‐sodium to creeping bentgrass, especially applications in the spring or fall or at cooler temperatures (Lycan and Hart, 2006; McCullough and Hart, 2006).…”
Section: Useful Conversionsmentioning
confidence: 98%
“…As such, paclobutrazol was the most effective product of those tested that is currently available for use on greens. Flurprimidol (Type II, Class B PGR) is another growth regulator option that has exhibited ABG suppression in putting greens but not as effective as paclobutrazol (Breuninger, 1993; Johnson and Murphy, 1995, 1996; Reicher et al, 2015). Future availability of herbicides such as methiozolin and bispyribac‐sodium would provide needed options to allow for the rotation or addition of multiple control strategies in an ABG control system to limit resistance development.…”
Section: Recommendations For Annual Bluegrass Controlmentioning
confidence: 99%
“…This is somewhat expected because vernalization and photoperiod requirements to initiate ABG flowering are variable across populations and thus are expected to differ across locations (Johnson & White, 1997a, 1997b). The differing level of response to Proxy applications is also not unexpected given the differential responses to herbicides and the growth regulator Trimmit (paclobutrazol) at different locations (Patton et al., 2019; Reicher et al., 2015).…”
Section: Practical Recommendations For Controlling Annual Bluegrass Smentioning
confidence: 99%
“…Data collected throughout the study included visual estimates of percent ABG seedhead cover per plot as well as turf injury (1 = dead, 5 = acceptable, and 9 = no injury) and turf quality (1 = dead, 5 = acceptable quality, and 9 = perfect turf). Seedhead cover measurements were plotted over days after initial spring application through final rating for each location presented as area under seedhead cover progress curve (AUSCPC), similar to other studies on ABG control (Askew, 2017; Reicher et al., 2015; Woosley, Williams, & Powell, 2003). The AUSCPC was calculated as: normalAUSCPC0.33em=i=1n1)(Xi+1+Xi-0.16em-0.16em/2false]ti+1ti…”
Section: Nationwide Evaluation Of Fall Applications For Suppressing Amentioning
confidence: 99%
“…P lant growth regulators like paclobutrazol [(2 S ,3 S ) ‐1‐(4‐chlorophenyl)‐4,4‐dimethyl‐2‐(1 H ‐1,2,4‐triazol‐1‐yl)‐3‐pentanol] and TE [ethyl 4‐(cyclopropyl[hydroxyl]methylene)‐3,5‐dioxocyclohexanecarboxylate] are applied to golf putting greens to reduce clipping yield and improve turfgrass color and density, as well as to enhance abiotic stress tolerance (Ervin and Zhang, 2008). Paclobutrazol has been shown to be useful to manage annual bluegrass ( Poa annua L.) encroachment on creeping bentgrass greens (Reicher et al, 2015). Both TE and paclobutrazol inhibit biosynthesis of the hormone gibberellin (GA) but are classified as either Class A or Class B PGRs in turf because they affect different processes within the pathway (Ervin and Zhang, 2008).…”
mentioning
confidence: 99%